A remote sensing approach to assess algal beta-carotene content in solar salt evaporation ponds - Komaristaya, V.; Bezrodnova, O.; Rudas, A. (ХНУ ім. В.Н. Каразіна, 2018)
The present research attempts to calibrate satellite images against field data on D. salina ß-carotene concentration expressed per 1 L of brine. We found the empirical relation between ß-carotene quantity and the index based on two infrared reflectance bands (NIR and SWIR).
Keywords: Dunaliella salina; beta-carotene; Landsat 5TM; Landsat 7ETM+; reflectance; near infra-red (NIR); short wave infra-red (SWIR)